Childhood Hyperuricemia as Risk Factor of Hypertension in Adulthood - Oke Rina Ramayani (The Indonesian Biomedical Journal, 2012)
BACKGROUND: Uric acid is the end product of purine metabolism. Hyperuricemia can occur because of decreased excretion, increased production and/or a combination of both mechanisms. Elevation of uric acid in the blood (>5.5 mg/dL) in children is associated with the occurrence of essential hypertension. The relevance of pediatric hyperuricemia into adult hypertension have been widely studied.CONTENT: The high percentage of children and adolescents with metabolic syndrome who had an elevated concentration of uric acid could be of great concern if it were concluded that uric acid was an independent risk factor for cardiovascular disease. The minimum age that has shown blood pressure is significantly associated with adult life is unknown. There are a number of possible explanations for the phenomenon of blood pressure tracking, including hyperuricemia. Several pathophysiological mechanisms increase uric acid with cardiovascular damage through proliferation of vascular smooth muscle cells, stimulate inflammatory path, and then prothrombotic effects triggered by the activation of platelets. Once vascular lesion has appeared, then arises the sodium-sensitive hypertension, although uric acid levels have returned to normal. Persistant mechanism of sodium sensitivity is caused by renal ischemia that leads to activation of the renin-angiotensin system, renal vasoconstriction and increased reabsorption of salt. This supports better understanding of the link between childhood hyperuricemia and adulthood hypertension.SUMMARY: Childhood hyperuricemia is an independent risk factor of hypertension and is ‘linked to’ adult blood pressure.KEYWORDS: uric acid, hyperuricemia, primary hypertension, children, adult